Evaluation outcomes of a knowledge translation platform: a structure for support and exchange in prevention. (1st February 2020) - Pettman, Tahna Lee; Armstrong, Rebecca; Johnson, Shae; Love, Penelope; Gill, Timothy; Coveney, John; Swinburn, Boyd; Allender, Steven
Abstract : Obesity prevention is an urgent public health priority that requires action at multiple levels. Collaboration between academics, policy and practice is necessary to ensure best-practice implementation. A national knowledge translation and exchange (KT) platform, the Collaboration of Community-based Obesity Prevention Sites (CO-OPS), was delivered and evaluated over three years (2013‐15). A mixed-methods evaluation used communications and website data, knowledge-brokering data, event evaluations, interviews and tracer searches to assess process (reach, delivery, quality, cost, uptake) and impact (use of tools/resources, networking, improvements in practice). Results included: 1) average 27% yearly membership growth (330 new members per year) in response to KT activities including tailored communications, stakeholder engagement, knowledge brokering and networking opportunities; 2) sustained website use with approximately 1200 visits/month and 73% unique visitors; and high access to networking and professional development information (120 hits/month), and best practice guidelines (60 hits/month); 3) higher uptake of face-to-face interactive strategies (for example, workshops) than online interactive strategies (for example, knowledge broker service) and higher uptake of passive KT (for example, website resources) than interactive KT strategies (for example, workshops); 4) the KT function of CO-OPS was clearly valued, and appeared to address a gap in implementation. A central coordinating KT platform provided support for best practice and exchange opportunities to a broad network of practice, policy and academic professionals. Simple KT strategies such as tailored, targeted online resources were useful for practice, whilst more intensive KT strategies were important for network engagement. Findings are applicable to other information-sharing networks where professionals address complex public health problems.